Analisis Kualitas Air Tanah di Sekitar TPA Bagendung, Cilegon - Tri Fatma Agustina; Diana Invindianty Hendrawan; Pramiati Purwaningrum (Universitas Trisakti, 2021)
This study aims to determine the quality of groundwater content at the residents around the Bagendung landfill including physical, chemical and biological qualities. Data analyzed using the Pollutant Index Method on groundwater to determine the quality of well water with the distribution of pollutants in residential areas around the Bagendung landfill and also determine the quality of ground water. This study focused on several aspects, such as physical quality of water, the distance of well water from pollutants, the physical condition of the well, drainage, and analysis of the physical condition of the latrine. BOD ranges from 3-6 mg/L while the class 1 quality standard is 2 mg/L. The results of heavy metal measurements, Fe and Mn at the TPA Bagendung are still below the quality standard. The content of e. coli in the resident’s well at point 4 in December 2019 was 230 MPN/100 ml, which seems to have exceeded the quality standard. Sampling in January 2020, all resident wells were contaminated with e. coli where the content of e. coli ranged from 1300 MPN/100 ml-2800 MPN/100 ml while the quality standar of e. coli was 100 MPN/100 ml. The water quality status of well range from 4.30-6.07 (light-moderate pollution). The pollutant distribution pattern of the leachate landfill is seen from the parameters BOD5, Fe, Mn, nitrite and fecal coliform influenced by elevation, slope and contour. The distribution of pollutants leads from TPA Bagendung to the northwest. The public perception states that well water were smells and tastes.